Pregaming among Latina/o emerging adults: Do acculturation and gender matter?. Issue 4 (2nd October 2019) - Perrotte, Jessica K.; Zamboanga, Byron L.; Lui, P. Priscilla; Piña-Watson, Brandy
ABSTRACT: Among ethnic minority groups, Latina/o emerging adults are most likely to engage in pregaming, a risky drinking practice. This study examined how U.S. acculturation and enculturation are associated with pregaming and the extent to which gender moderates this relation in a sample of 312 Latina/o emerging adults (18 – 25 years of age). Results indicated that men consumed more alcohol when pregaming than women, but there were no gender differences in pregaming frequency. Results also showed that lower levels of U.S. acculturation were associated with greater alcohol consumption while pregaming for men, but not women. Gender did not moderate the association between acculturation and pregaming frequency. This study highlights the need to account for gender when examining sociocultural determinants of high risk drinking behaviors such as pregaming among Latina/o emerging adults.